Induced Pluripotent Stem Cells and Disorders of the Nervous System: Progress, Problems, and Prospects. (December 2013) - Faiz, Maryam; Nagy, Andras
Advances in cellular reprograming have shown that the delivery of specific transcription factors can result in the shift of one cell type to another. Brief forced expression of the four Yamanaka reprogramming factors (Klf4, Sox2, c-Myc, and Oct4) is able to convert many cell types into induced pluripotent stem cells, whereas some lineage specific transcription factors can convert cells from one type directly to another. Numerous strategies have already been developed for deriving neural cell types, with the hopes of better understanding/alleviating neurodegenerative disease. These cells facilitate drug discovery and constitute an autologous source of cells for brain repair, thus, avoiding rejection issues faced by allografts derived from embryonic stem cells. However, proper characterization of the various types of reprogrammed cells and an understanding of how these cells acquire neural fate is necessary before their translation into the clinic. Here, we review the progress, problems, and prospects with reprogrammed cell types with regards to neurodegenerative disease.